A Time-Series Analysis of Climate Variability in Urban and Agricultural Sites (Rome, Italy) - Luca Salvati; Ilaria Zambon; Giuseppe Pignatti; Andrea Colantoni; Sirio Cividino; Luigi Perini; Giorgio Pontuale; Massimo Cecchini (Agriculture, 2019)
Identifying early signals of climate change and latent patterns of meteorological variability requires tools analyzing time series data and multidimensional measures. By focusing on air temperature and precipitation, the present study compares local-scale climate regimes at two sites in Central Italy (urban Rome and a peri-urban cropland 10 km west of Rome), using descriptive and inferential statistics on both variables and a drought index (the Standardized Precipitation Index, hereafter SPI) recorded over the last 60 years (1958−2017). The present work assumes the importance of urban-rural gradients shaping local-scale climate regimes and spatial variability, with differential impacts on individual variables depending on territorial background and intrinsic biophysical characteristics. Considering together precipitations and minimum/maximum air temperature at month and year scale, the analysis developed here illustrates two coexisting climatic trends at distinctive spatial scales: A general trend toward warming—specifically influencing temperature regimes—and a more specific pattern evidencing changes in local-scale climate regime along the urban gradient, with a more subtle impact on both precipitations and temperatures. Empirical results indicate that climate variability increased over the study period, outlining the low predictability of dry spells typical of Mediterranean climate especially in the drier season (spring/summer). On average, absolute annual differences between the two sites amounted to 70 mm (more rainfall in the peri-urban site) and 0.9 °C (higher temperature in the urban site). A similar trend toward warming was observed for air temperature in both sites. No significant trends were observed for annual and seasonal rainfalls. SPI long-term trends indicate high variability in dry spells, with more frequent (and severe) drought episodes in urban Rome. Considering together trends in temperature and precipitation, the ‘urban heat’ effect was more evident, indicating a clearer trend toward climate aridity in urban Rome. These findings support the adoption of integrated strategies for climate change adaptation and mitigation in both agricultural systems and relict natural ecosystems surrounding urban areas.